INDUKSI EMBRIOGENESIS MIKROSPORA Nicotiana tabacum L. cv. Vorstenlanden DENGAN STRES PANAS DAN PELAPARAN - Zuchrotus Salamah (Universitas Muhammadiyah Semarang, 2004)
The aims of this research is to know the effect of heat shock 34oC and starvation of the tobacco, Nicotiana tabacum L. cv. Vorstenlanden microspore. Isolated microspore subjected to stress by culturing in starvation B medium and incubated at 34 oC for 7 days in dark. After 7 days in starvation medium the microspore were subcultured to theen-rbriogenesis medium (A2 mediun-r), incubated in dark during 4 weeks at25u C. Result slrowed that late uninucleat microspore was found in the bud with flower erown size (9-10) mm with precentage of 69%. After stres cytoplasm of the microspore nrorfologycally change, showed star like (tipe-3) 21% . Multicellular microspore was for